2005
DOI: 10.1021/jf040322c
|View full text |Cite
|
Sign up to set email alerts
|

Content and Molecular Weight of Extractable β-Glucan in American and Swedish Oat Samples

Abstract: beta-(1-->3),(1-->4)-D-Glucan (beta-glucan) was extracted from 93 Swedish and 41 American oat samples using hot water containing CaCl(2) and thermostable alpha-amylase. The samples showed a large variation in both the content of extractable beta-glucan (0.76-3.68%) and the average molecular weight ((1.25-1.78) x 10(6) g mol(-1)). An analysis of the variance of beta-glucan content and the molecular weight of Swedish oat samples grown in 2000 and 2001 was done with cultivar and harvest year as factors. It showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 13 publications
6
43
2
1
Order By: Relevance
“…The average MW of high-MW β-glucan extracted from N979 oat was similar to that of the Jim oat, but the peak MW of N979 was greater than that of the Jim oat line, likely because of differences in heritable traits of oat lines. 30 The peak and final viscosities of the high-, medium-, and low-MW β-glucan suspensions from Jim and N979 oats were determined by using the RVA at 25°C ( Table 1). The viscosity of the suspensions decreased greatly with a decrease in MW of β-glucan (p < 0.05).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The average MW of high-MW β-glucan extracted from N979 oat was similar to that of the Jim oat, but the peak MW of N979 was greater than that of the Jim oat line, likely because of differences in heritable traits of oat lines. 30 The peak and final viscosities of the high-, medium-, and low-MW β-glucan suspensions from Jim and N979 oats were determined by using the RVA at 25°C ( Table 1). The viscosity of the suspensions decreased greatly with a decrease in MW of β-glucan (p < 0.05).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…With this detection technique, molecules smaller than 10 4 are excluded from the analysis. Most of the samples were extracted for 1.5 h, except those containing oats, which were extracted for 6 h in boiling water in the presence of thermostable a-amylase (Ajithkumar, Andersson, & Åman, 2005). Fructan quantification was performed according to McCleary, Murphy, and Mugford (2000) using a spectrophotometric method with the enzymatic assay kit K-FRUC (Megazyme, Bray, Ireland).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of oats in breakfast cereal and barley flour in crisp bread, along with short treatment time and low water activity, can explain the high values in the extruded products. It is well established that both oats and barley have higher molecular weights than rye (Ajithkumar et al, 2005;Andersson, Lampi, et al, 2008;Cyran, Courtin, & Delcour, 2003).…”
Section: %mentioning
confidence: 99%
“…b-Glucan derived from oats is a linear, unbranched, nonstarch polysaccharide of b-D-glucose with 1 1b~3 linkage for every 3 or 4 1b~4 linkages. 42,68 A meta-analysis of 67 controlled dietary studies showed that for each gram of soluble fiber from oats, psyllium, or pectin, the levels of total cholesterol and LDL cholesterol decreased by approximately 1.55 mg/dL (0.045 mmol/L), with no effect on triglyceride or HDL cholesterol levels. 22 The observed changes appeared to be independent of study design, length of treatment, and dietary fat content.…”
Section: J) Group A: American Heart Associationmentioning
confidence: 99%